Mini-Review: The Influence of Coating and Doping on The Crystal Volume and Discharge Capacity of Lithium Iron Phosphate-Based Materials as Battery Cathode - Intifadhah, Sahara Hamas; Syaima, Husna (Jurnal Kumparan Fisika, 2024)
ABSTRAK   Baterai ion litium adalah jenis baterai isi ulang yang memiliki kapasitas tinggi, potensi elektrokimia yang baik, dan daya tahan yang kuat. Perkembangan LiFePO4 sebagai material katoda baterai ion litium semakin meningkat dengan adanya beberapa teknik tambahan dalam proses sintesis untuk meningkatkan performa seperti teknik pelapisan dan penyisipan atom. Hal tersebut mempengaruhi volume kristal, serta sifat elektrokimia material berbasis LiFePO4. Metode pelapisan yang menunjukkan peningkatan nilai kapasitansi material berbasis LiFePO4. Sedangkan pada metode penyisipan atom, beberapa penelitian menggunakan atom Ce, Ru, Co, Na, Si, Mn, Zn dan In untuk disisipkan di atom Fe, Li, atau P pada material berbasis LiFePO4. Hasil yang diperoleh dari beberapa penelitian tentang sintesis material katoda LiFePO4 menunjukkan adanya peningkatan kapasitas discharging dan peningkatan volume kristal olivine, sehingga teknik pelapisan dan penyisipan ini dapat digunakan untuk peningkatan performa elektrokimia.   Kata  kunci: LiFePO4, Pelapisan, Penyisipan, Volume Kristal, Kapasitansi   ABSTRACT   Lithium-ion batteries are a type of rechargeable battery that has high capacity, good electrochemical potential, and strong durability. The development of LiFePO4 as a cathode material for lithium-ion batteries has been increasing with the addition of several techniques in the synthesis process to enhance performance, such as coating and atom insertion techniques. These techniques affect the crystal volume and the electrochemical properties of LiFePO4-based materials. Coating methods have shown improvements in the capacitance values of LiFePO4-based materials. Meanwhile, in atom insertion methods, some studies have used Ce, Ru, Co, Na, Si, Mn, Zn, and In atoms to be inserted into Fe, Li, or P atoms in LiFePO4-based materials. Results from several studies on the synthesis of LiFePO4 cathode materials have shown an increase in discharge capacity and an increase in the volume of olivine crystals, indicating that coating and insertion techniques can be used to improve electrochemical performance.   Keywords: LiFePO4, Doping, Coating, Crystal Volume, Capacity